PENGARUH JALAN KAKI DAN RELAKSASI NAPAS DALAM (JAKARENA) TERHADAP KADAR GULA DARAH KELOMPOK PREDIABETES - Waluya, Nandang Ahmad; Sakti, Bani; Hamzah, Ali (Poltekkes Kemenkes Bandung, 2024)
The prevalence of prediabetes (preDM) in Indonesia is increasing, posing a significant risk for developing Diabetes Mellitus (DM). The American Diabetes Association (ADA) predicts that approximately 70% of individuals with preDM will progress to diabetes. Globally, the number of people with DM is projected to reach 693 million by 2045. In 2019, Bandung City reported 45,430 individuals with DM. Prediabetes management necessitates a comprehensive approach, including lifestyle modifications such as increased physical activity, exercise, and dietary control. This study aimed to investigate the effect of a combined walking and deep breathing relaxation exercise program (JAKARENA) on blood glucose levels in individuals with preDM. This analytical study employed a quasi-experimental design with a Non-equivalent Group Pre-test-Post-test design. The population comprised adults with preDM, with 46 participants selected through purposive sampling and divided into intervention and control groups. Data analysis utilized the Independent T-test. Results demonstrated that the mean baseline blood glucose level in the control group (108.39 mg/dl) was lower than that of the intervention group (111.00 mg/dl). Post-intervention, the control group exhibited a slight increase in blood glucose levels (109.65 mg/dl), whereas the intervention group experienced a significant decrease (102.75 mg/dl). The statistical analysis yielded a p-value of 0.001, indicating a statistically significant effect of JAKARENA on reducing blood glucose levels in individuals with preDM. Conclusion: JAKARENA exercise demonstrates the potential to effectively lower blood glucose levels in individuals with preDM and can be recommended as a valuable community-based intervention to mitigate the progression of preDM to DM.